The Impact Of Government Spending On Employment In Syria During The Period 1990-2011 (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aims to determine the relationship between tax revenues and the unemployment rate in Syria during the period 1990 -2010, by studying the co-integration between the variables according to the Autoregressive Distributed Lag model ARDL . The study concluded that there is an equilibrium relationship in the long term between unemployment rates and tax revenues, both direct and indirect, in addition to a relationship in the short term according to the ESM error correction model, where the correction coefficient was 0.6901, which means ,in the long term  if a shock has been happened  at the level of the unemployment rate  we need 1.5 years to return to equilibrium in the long term .